Destination image, unforgettable traveling experience, and revisit intention: Viewpoint from tourists visiting cultural attraction - Dagustani, Asyrafil Herza; Tjahyadi, Rully Arlan; Hadianto, Bram (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
Bandung is recognized as a flower city because of its beauty. Besides, it provides several destinations for tourists. One is Saung Angklung Udjo (SAU), oriented to Sundanese culture. For the tourism business, the revisiting intention of tourists becomes valuable for its sustainability. Therefore, this study reveals the determinant of revisiting intent. According to previous research, they are a destination image and an unforgettable traveling experience. In other words, this study aims to check and analyze three effects. The first and second are the influence of destination image on revisiting intention and unforgettable traveling experience. The third is the impact of the memorable touring experience on this intention. Then, to achieve this purpose, it employs 169 domestic tourists visiting SAU as the sample and the covariance-based structural equation model with its feature to examine three hypotheses formulated. After investigating them, this study concludes destination image positively affects revisit intention and unforgettable traveling experience. Similarly, this positive sign exists for the relationship between this experience and intention.